Utilizing point-of-care A1c to impact outcomes – can we make it happen in primary care?. Issue 1 (9th February 2022) - Rhyu, Jane; Lambrechts, Sylvia; Han, Maria A.; Freeby, Matthew J.
Abstract : Purpose of review: Hemoglobin A1c testing provides a marker of glycemic control and is the standard for diabetes risk assessment. According to the Centers for Disease Control (CDC), only 67.3–71.4% of diabetic patients between 2011 and 2016 had at least two A1c levels tested per year. Moreover, 27.8% had uncontrolled diabetes with an A1c of ≥8.0%, increasing the risk of microvascular complications. Lack of monitoring presents a significant barrier, and improving ease of testing could improve glycemic control. Recent findings: Point-of-care (POC) A1c testing, obtained via capillary blood with results provided in 5–6 min, is available and used frequently in endocrine clinics. However, POC A1c testing is not standard in primary care, where 90% of type 2 diabetes patients are treated. Barriers include access and costs of POC A1c machines and standardization of testing in the primary care setting. Review of literature, however, suggests that POC A1c testing in primary care may lead to A1c reduction whereas being potentially cost-effective and strengths the patient–physician relationship. Summary: POC A1c testing in primary care, if widely available and integrated into workflow, has the potential to positively impact diabetes care. Real-time feedback may change patient and physician behaviors, allowing earlier therapeutic intensification.